Indikator Motivasi Kerja Da’i , Manfaat dan Tujuannya (Kajian dalam Manajemen Komunikasi Dakwah) - Hasan, Yummil (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The level of work motivation is based on two aspects which are indicators, namely motivator factors and health or maintenance factors. The motivator factor is a factor or situation that can encourage achievement and intrinsic in nature that comes from within the da'i itself. This motivator factor relates to opportunities for achievement, opportunities to gain recognition, advances, opportunities in the work itself, personal improvement or development and opportunities to obtain responsibility. While hygiene / sanitation factors are extrinsic factors which are derived from outside the preacher, but also determine the behavior of preachers in carrying out their work and related to the environment in which the work is carried out. Hygiene factors will provide satisfaction (satisfies) if these factors are met, on the contrary if it is not fulfilled it will cause dissatisfaction (dissatisfaction) which will cause demands for the da'i.